Understanding the Dynamic Behaviour of the Google Congestion Control for RTCWeb - Luca De Cicco; Gaetano Carlucci; Saverio Mascolo (2013 20th International Packet Video Workshop, 2013)
Real-time communication over the Internet is of ever increasing importance due the diffusion of portable devices, such as smart phones or tablets, with enough processing capacity to support video conferencing applications. The RTCWeb working group has been established with the goal of standardizing a set of protocols for inter-operable real-time communication among Web browsers. In this paper we focus on the Google Congestion Control (GCC), recently proposed in such WG, which is based on a loss-based algorithm run at the sender and a delay-based algorithm executed at the receiver. In a recent work we have shown that a TCP flow can starve a GCC flow. In this work we show that this issue is due to a threshold mechanism employed by the delay-based controller. By carrying out an extensive experimental evaluation in a controlled testbed, we have found that, when the threshold is small, the delay-based algorithm prevails over the loss-based algorithm, which contains queuing delays and losses. However, a small threshold may lead to starvation of the GCC flow when sharing the bottleneck with a loss-based TCP flow.
Keywords: Delays; Bandwidth; Google; Peer-to-peer computing; Receivers; Detectors; Streaming media